INSTITUTIONAL CHALLENGES AND LECTURERS’ JOB SATISFACTION IN PUBLIC UNIVERSITIES IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2026)
This study examined the institutional challenges and lecturers’ level of job satisfaction in publicuniversities in Anambra State. Four research questions guided the study. A descriptive surveyresearch design was employed in the study. Population for the study comprised 3,247 lecturersfrom two public universities in Anambra State. Sample size of the study constituted 1,624lecturers from the total population selected using proportionate stratified random samplingtechnique. A researcher-developed 36-item questionnaire titled: “Institutional Challenges andLevel of Lecturers Job Satisfaction Questionnaire (ICLLJSQ)” and structured on a 4-point ratingscale, served as instrument for data collection. Both validity and reliability of questionnaire wasestablished. Data collated were analyzed using mean statistics rated at 2.50 and standarddeviation statistics. Findings indicated a generally low level of lecturers’ job satisfaction arisingfrom all the identified institutional challenges as regards to the working conditions, research andacademic support, administrative leadership, and remuneration challenges. The studyrecommended among others that the University managements in collaboration with government(both federal and state) and relevant stakeholders, should prioritize the improvement of lecturers’working conditions to curb certain relative challenges through the provision and maintenance ofadequate office spaces, modern teaching facilities, functional laboratories, reliable internetservices, and stable power supply, in order to increase lecturers’ high level of job satisfaction.
Keywords: Institutional, Challenges, Lecturers, Job, Satisfaction